The anime boom in the United States lessons for global creative industries - Daliot-Bul, Michal; Otmazgin, Nissim (Harvard East Asian monographs, 2017)
"Drawing on in-depth interviews with Japanese and American animation industry professionals, field research, and market surveys, this book investigates the ways anime has been exported to the U.S. since the 1960s, exploring the transnational networks of anime production and marketing while also investigating the cultural and artistic processes it inspired"--